Impact of Brexit on the trade of Hungarian agricultural and food products - Vásáry Miklós (Review on agriculture and rural development, 2019)
As a result of the longer preparation process, 51.9% of voters voted in the UK on 23 June 2016 in the form of a referendum to leave the European Union. Although the negotiation process has begun, many decisive points and principles - the negotiators' agreement on the post-exit process - have not decided at the beginning of 2019. The fact that the United Kingdom officially withdraws from the European Union will significantly transform bilateral trade relations. Through the – till now – fruitful cooperation, both sides were able to take advantages and thus have achieved substantial economic benefits, economic and welfare growth. It seems that the UK has been more in need of its trade, so it is becoming increasingly important on what conditions the new cooperation will operate. But it may also be important to see how the British exit will affect Hungary. Within this framework, one specific area of trade policy, the analysis and evaluation of agri-food processes, should be carried out. Although there is a significant geographical distance between the two countries, there has been a growing and significant commercial activity due to the favorable trade effects. The purpose of this study is to structure the trade effects between the agri-food industry. In addition, there is a need to organize the affected branches and expected effects too.